Youth in postwar Guatemala : education and civic identity in transition - Bellino, Michelle J., 1980- (Rutgers series in childhood studies., 2017)
"In the aftermath of armed conflict, how do new generations of young people learn about peace, justice, and democracy? Michelle J. Bellino describes how, following Guatemala's civil war, adolescents at four schools in urban and rural communities learn about their country's history of authoritarianism and develop civic identities within a fragile postwar democracy. Through rich ethnographic accounts, Youth in Postwar Guatemala, traces youth experiences in schools, homes, and communities, to examine how knowledge and attitudes toward historical injustice traverse public and private spaces, as well as generations. Bellino documents the ways that young people critically examine injustice while shaping an evolving sense of themselves as civic actors. In a country still marked by the legacies of war and division, young people navigate between the perilous work of critiquing the flawed democracy they inherited, and safely waiting for the one they were promised"--